2012
DOI: 10.1007/s11571-012-9192-2
|View full text |Cite
|
Sign up to set email alerts
|

Brain fingerprinting: a comprehensive tutorial review of detection of concealed information with event-related brain potentials

Abstract: Brain fingerprinting (BF) detects concealed information stored in the brain by measuring brainwaves. A specific EEG event-related potential, a P300-MERMER, is elicited by stimuli that are significant in the present context. BF detects P300-MERMER responses to words/ pictures relevant to a crime scene, terrorist training, bombmaking knowledge, etc. BF detects information by measuring cognitive information processing. BF does not detect lies, stress, or emotion. BF computes a determination of ''information prese… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
165
3
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 79 publications
(185 citation statements)
references
References 78 publications
6
165
3
1
Order By: Relevance
“…Th e subsequent analyses showed that the average value of the P300 amplitude was signifi cantly higher in the group of the 'guilty' subjects, who tried to conceal removing the object than in the group of the 'innocent' (Rosenfeld, Cantwell, Nasman, Wojdac, Ivanov, Mazzeri 1988, after: Rosenfeld 1999. At the same time, studies of the possibility of detecting deception through analysis of the P300 potential amplitude were conducted also by Farwell and Donchin, who presented their results at a conference of the Society for Psychophysiological Research already in 1986 (Farwell andDonchin 1986 after: Rosenfeld 2011), and published them fi ve years later (Farwell, Donchin 1991).…”
Section: Th E P300 Potential and Polygraph Examinationsmentioning
confidence: 99%
See 1 more Smart Citation
“…Th e subsequent analyses showed that the average value of the P300 amplitude was signifi cantly higher in the group of the 'guilty' subjects, who tried to conceal removing the object than in the group of the 'innocent' (Rosenfeld, Cantwell, Nasman, Wojdac, Ivanov, Mazzeri 1988, after: Rosenfeld 1999. At the same time, studies of the possibility of detecting deception through analysis of the P300 potential amplitude were conducted also by Farwell and Donchin, who presented their results at a conference of the Society for Psychophysiological Research already in 1986 (Farwell andDonchin 1986 after: Rosenfeld 2011), and published them fi ve years later (Farwell, Donchin 1991).…”
Section: Th E P300 Potential and Polygraph Examinationsmentioning
confidence: 99%
“…A solution to this problem, namely the use of the bootstrapping method, was proposed in the studies by Farwell andDonchin (1986, after: Wasserman andBockenholt 1989;Farwell and Donchin 1991). Application of that method makes it possible to obtain an entire distribution of average potentials for the signifi cant stimulus through sampling with replacement of sets that contain X 4 individual iterations after the presentation of the signifi cant stimulus and their subsequent averaging (Wasserman and Bockenholt 1989).…”
Section: Guilty or Innocent? Individual Assessment Proceduresmentioning
confidence: 99%
“…By recording EEG in the cognitive processing of case relevant content, the relationship between the person taking the test and the case was analyzed. At present, the most common identification index of ERPs deception detection was P300, thus it was also called P300 deception detection technology [10].…”
Section: Introductionmentioning
confidence: 99%
“…In some countries, the ERPs technology with MERMER as an indicator has been applied in practice, such as spy recognition, case investigation etc. Farwell uses words and phrases as stimulus to detect the feasibility and accuracy of MERMER as a deception detection tool [10].…”
Section: Introductionmentioning
confidence: 99%
“…Among these brain signals, P300 event-related potential (ERP) has been widely used in electroencephalography (EEG)-based BCI systems (Farwell 2012). It relies on the fact that, infrequent stimuli, when interspersed with routine stimuli, typically evoke a positive peak at about 300 ms (Bernat et al 2001).…”
Section: Introductionmentioning
confidence: 99%